Delignification of Bana Grass Using Sodium hydroxide and Ozone - Jurarut Minmunin (2018)
© 2017 Springer Science+Business Media B.V. In this work, Bana grass, a species of Napier grass (P. purpureum × P. americanum hybrid) which contains 60.2% cellulose, 23.8% hemicellulose and 8.2% lignin, was tested in the laboratory for lignin removal or delignification. Two processes of delignification were combined. Firstly, alkali pretreatment was used to determine the best conditions for the first stage of delignification. Secondly, the selected pretreated material, which was obtained from the best conditions for the first stage, was tested with the ozonolysis process. In the first stage of alkali pretreatment, five concentrations of sodium hydroxide (NaOH) from 0.5 to 10.5 wt.% were used. This research considers the ratio of cellulose to lignin because the ratio should be high for good lignocellulose. For untreated Bana grass, the ratio of cellulose to lignin is 7.3. After the first stage of alkali pretreatment, the maximum cellulose and lignin ratio is at 12.6 with 5.5 wt.% NaOH, and the amount of lignin elimination is 5.2%. The second stage is to pretreat lignocellulose with ozone. The concentration of ozone in the experiment is 1000 mg/h, and the pretreatment time is 0–30 min. Increasing time leads to higher lignin removal, but there is still cellulose in the material. Ozone pretreatment increases the ratio of cellulose to lignin for the first stage pretreatment material to 93.8. Ozone pretreatment alone cannot eliminate lignin from Bana grass, but it is better if it reacts with a sodium hydroxide solution. A combination of alkali and ozone pretreatment gives a high ratio of cellulose to lignin. From the results of the inhibitor examination, it is found that there is no detection of acetaldehyde, but total phenolics are detected for the pretreatment condition. These toxins can be eliminated by washing with water.